Tacrolimus (FK506) promotes placentation and maternal-fetal tolerance through modulating FASN-CEACAM1 pathway - Meng, Xinhang; Shi, Minfeng; Qian, Jinfeng; Luo, Yujie; Cui, Liyuan; Li, Dajin; Wang, Songcun (Frontiers in Immunology, 2025)
The establishment of placentation and maternal-fetal tolerance are important determinants of a successful pregnancy. Tacrolimus, also known as FK506, is a calcineurin inhibitor that has often been used for pregnant women after solid organ transplantation. Previous therapeutic interventions have shown the benefits of using the immuno-suppressive agent FK506 in improving clinical pregnancy and live birth rates and reducing the risk of spontaneous miscarriage. However, the mechanism(s) by which FK506 is involved in these processes have not been fully elucidated. To further characterize its function in early pregnancy, we explored the effect of FK506 on the human-derived first trimester extravillous trophoblast cells (HTR8/SVneo cells) and found that FK506 promoted invasion, tube formation and proliferation, but inhibited apoptosis of HTR8/SVneo cells. Based on the integrated metabolomics and transcriptomics analyses, the present study provided the cellular and molecular cues evidently showing that FK506 had positive effects on the placentation and maternal-fetal tolerance through modulating FASN-CEACAM1 pathway. The spontaneous-abortion-prone model gave further evidence that FK506 exerted a protective effect on pregnancy by regulating the FASN-CEACAM1 axis. These findings might provide a new fundamental mechanism and promising potential of low-dose FK506 in preventing pregnancy loss.